Impact of Information and Communication Technology on The Welfare of Population in Eastern Indonesia - Dyah Makutaning Dewi; Istu Indah Setyaningsih; Ariful Romadhon (Politeknik Statistika STIS, 2021)
During the Covid-19 pandemic, many countries in the world are expected to experience a slowdown or decrease in Human Development Index (HDI) growth including Indonesia. The disparities in development among regions to be one of the main issues in Indonesia. The gaps are not only occurring in HDI, but also in Information and Communication Technology (ICT) facilities between Western Indonesia and Eastern Indonesia. The purpose of this study is to analyze how Information and Communication Technology affects the Welfare of the Population in Eastern Indonesia. Research methods use multiple linear regression methods. The data is sourced from the BPS-Statistics Indonesia which consists of 17 provinces. The results showed that the percentage of internet users had a positive and significant effect while the percentage of the poor population had a negative and significant effect on the welfare of the population in eastern Indonesia. Therefore, the distribution of infrastructure, especially ICT infrastructure, does not only focus on western Indonesia. Therefore, it is expected that the population welfare gap will be reduced. The increasing use of the internet during the Covid-19 pandemic can be used as an opportunity to be used as a bridge for the distribution of information, communication, and digital-based economic development in order to achieve equitable welfare, especially in eastern Indonesia.